Pengaruh Kinerja Keuangan Terhadap Keputusan Investasi Perusahaan - Nuradilah, Ayu; Rahayu, Nurrisma; Octavia, Putri; Meilani, Tria; Suherman, Ujang (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Finance refers to the financial condition of a company over a certain period of time, which includes features of increasing and distributing capital. These features are usually measured using capital adequacy, liquidity, and profitability metrics (Jumingan, 2006). By analyzing the financial data contained in the company's financial reports, it is possible to determine developments in financial performance (Wijayanto, 2021). Investors will use strong financial performance as a standard to guide investment decisions. Investment is the process of investing money into one or more assets over a certain period of time with the intention of growing the investment and/or earning income (Harianto, F. and Sudomo, 2021). There are two types of investment: conventional investment and sharia investment.